Pengaruh Murottal Al-Qur’an Surah Ar Rahman Terhadap Kualitas Tidur Mahasiswa Fakultas Kedokteran Universitas Jember - Ratrinda, Musdalifana Vega; Wiryaning Putri, Komang Yunita; Sofiana, Kristianningrum Dian (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2023)
Background:Medical students are at risk for experiencing sleep disturbances due to the demands of the academic assignments they face. Al-Quran murottal therapy is a sound therapy that is given to someone to have a relaxing effect Objectif : This study aims to determine the effect of murottal AlQuran on sleep quality of medical students, University of Jember Methods :This type of research is quasi experimental with one group pretest-postest design. The research was carried out for 1 week listen to the murotal Al Quran Surah Ar Rahman read by Qori Misyari Rasyid Al Afasy for 15 minutes at the respondent's location using the zoom application. The sample of this research was 18 students of medical student, University of Jember, class of 2018 and 2019. Samples were taken using the technique purposive sampling. Data were analyzed univariately and bivariately using testwilcoxon signed rank test and carried out the normality test using shapiro wilk Results: The results of the univariate analysis showed changes mean sleep quality pretest and posttest. Before listening to murottal Al-Quran have mean 8.16 and after listening to the Al-Quran to 3.66. The result of bivariate analysis is test wilcoxon signed rank test value is obtained p-value= 0.000 indicates that there is a significant difference between the provision of murottal Al-Quran and the sleep quality of medical students, University of Jember Conclusion : The conclusion of this study is that there is an effect of murottal AlQuran on improving the sleep quality of medical students, University of Jember